Stimulation of phenolic nature secondary metabolites biosynthesis in Echinacea purpurea L. Moench suspension cell cultures under influence yeast extract elisitors - Nester, Grazhina V.; Ditchenko, Tatyana I. (Experimental Biology and Biotechnology, 2020)
Тhe ability of 50 ‒500 mg / L yeast extract as complex biotic elicitor to induce an increase in the accumulation of secondary phenolic metabolites in Echinacea purpurea L. Moench suspension cell cultures initiated from calli of leaf and root origin was studied. The yeast extract stimulating effect is more pronounced for a weakly aggregated suspension culture of leaf origin compared with a root origin culture of highly aggregated type. The increase of phenylpropanoids (2.5 times) and flavonoids (2.0 times) content in aqueous-alcoholic extracts from leaf culture as a result of 2-day exposure to 100 ‒500 mg/L of yeast extract correlates with their antiradical activity increase in model system for 2,2ʹ-diphenyl-1-picrylhydrazyl radicals inhibition. The exposure of suspension cell cultures of leaf and root origin in the presence of 250 ‒500 mg/L yeast extract leads 2.1‒2.7 and 1.2‒1.3 times increase L-phenylalanine ammonium lyase activity as key enzyme of phenolic compounds biosynthesis.